2010
DOI: 10.1155/2010/316170
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Its Individual Components among Jordanian Children and Adolescents

Abstract: This study aimed to determine the prevalence of metabolic syndrome (MeS) and its individual components in Jordanian children and adolescents aged 7–18 years and determine the factors that are associated with clustering of metabolic abnormalities. MeS was defined using the International Diabetes Federation (IDF) definition. The prevalence of MeS was estimated from 512 subjects who had complete information on all MeS components. The prevalence of MeS according to IDF criteria was 1.4% in subjects aged between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
8
1
Order By: Relevance
“…Body weight (kg), height (cm) and waist circumference (cm) were measured for all subjects as previously described (20). BMI was determined for all subjects according to the formula: BMI = body weight (kg)/height (m 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Body weight (kg), height (cm) and waist circumference (cm) were measured for all subjects as previously described (20). BMI was determined for all subjects according to the formula: BMI = body weight (kg)/height (m 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Details of the study design are reported elsewhere [23,24]. Briefly, a complex multistage sampling technique was used to select the households, taking into consideration the geographic distribution of the population as well as the urban-rural residence.…”
Section: Methodsmentioning
confidence: 99%
“…In the Pressioni Arteriose Monitorate E Loro Associazioni (PAMELA) population study, high normal or frank hypertension was noted in greater than 80% of studied individuals who met the CMS criteria. Less common was visceral obesity, lipid abnormalities, and impaired fasting glucose [41].…”
Section: Cardio Metabolic Syndrome Risk Factors and Associated Healthmentioning
confidence: 99%
“…Hypertension is defined as Systolic Blood Pressure (SBP) ≥ 140 mm Hg or Diastolic Blood Pressure (DBP) ≥ 90 mm Hg [41]. In the Pressioni Arteriose Monitorate E Loro Associazioni (PAMELA) population study, high normal or frank hypertension was noted in greater than 80% of studied individuals who met the CMS criteria.…”
Section: Cardio Metabolic Syndrome Risk Factors and Associated Healthmentioning
confidence: 99%